Pengaruh Aspek Sosial-Politik dan Ekonomi Terhadap Ketimpangan Pendapatan di Indonesia - Anti, Yuni Yuli; Anis, Ali (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
This research aims to determine the influence of socio-political and economic aspects on income inequality in Indonesia in 2017-2021. This research uses Fixed Effect Model (FEM) analysis using Stata 14. The results of research using panel data regression show that: 1). The social aspect proxied by education has an insignificant negative influence on income inequality in Indonesia. 2). Social aspects proxied by health have an insignificant negative influence on income inequality in Indonesia. 3). The political aspect proxied by the Indonesian democracy index has an insignificant positive influence on income inequality in Indonesia. 4). The economic aspect proxied by GRDP has a significant negative influence on income inequality in Indonesia. 5). Independent variables have a simultaneous or joint effect and are significant on the dependent variable.